Elements of Social Learning Approach in Managing Forest as a Common Property: A Perspective from the ANRM from a Hill Village of Eastern Nepal - Uprety, Laya Prasad (Himalayan Journal of Sociology and Anthropology, 2009)
No abstract available DOI: http://dx.doi.org/10.3126/hjsa.v2i0.1582 Himalayan Journal of Sociology & Anthropology Vol.2 2005 p.88-132